TAPESTRIES OF CREATIVITY: PRIVILEGE, OPPRESSION, AND DISCOMFORTING EMOTIONS IN THE CLASSROOM - Clarke, Samantha; Dutta, Debashis; Adamowich, Todd (Canadian Social Work Review / Revue canadienne de service social)

(untitled) (Canadian Association for Social Work Education / Association canadienne pour la formation en travail social (CASWE-ACFTS), 2024)
The front-line people skills and interventions that social workers use are shaped by their personal experiences of race, culture, socioeconomic status, sexual orientation, gender, gender expression, ability and disability, and religion and spirituality, as well as by the specific time and geopolitical contexts in which they practice. Social workers are taught to identify and be cognizant of these aspects of their social location when they are BSW students. In this regard, they submit papers and deliver presentations designed to demonstrate their reflexivity and ability to integrate theory into practice. However, these evaluations do not adequately capture how their learning influences them as emergent professionals. Creativity and artwork transcend traditional academic learning by engaging the senses in ways that personalize each student’s learning experience while supporting their fellow learners. As such, the focus of creative social work education is directed at both the process of creativity and the product of that process, namely the creation. Using a transformative learning lens, this research examined how BSW students incorporated their creative expressions in the classroom, as a process toward using self-reflexivity as a skill to further their transformative learning about social justice.